2014
DOI: 10.1080/00140139.2013.869357
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting skill decay: four refresher interventions and their effect on skill and knowledge retention in a simulated process control task

Abstract: In process automation, skill decay has not been investigated systematically. In two experimental studies, refresher interventions (RIs) were compared to support skill and knowledge retention of a start-up procedure on a simulated process control task. Based on theories of proceduralisation, the 'testing-effect' and mental practice, four different RIs were designed. In Study 1 (N = 68), two experimental groups (EGs) received either an RI called 'Practice' or an RI called 'Skill Demonstration'. Both RIs support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
2
50
0
1
Order By: Relevance
“…Previous research has found that refresher interventions support the retention of once-learned skills and are particularly important for procedural skills (Farmer, Van Rooij, Riemersma, Jorna, & Moraal, 1999;Kluge & Frank, 2014). A refresher intervention aims to re-establish a specific skill level that was acquired at the end of initial training.…”
Section: Refresher Interventions and Skill Retentionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has found that refresher interventions support the retention of once-learned skills and are particularly important for procedural skills (Farmer, Van Rooij, Riemersma, Jorna, & Moraal, 1999;Kluge & Frank, 2014). A refresher intervention aims to re-establish a specific skill level that was acquired at the end of initial training.…”
Section: Refresher Interventions and Skill Retentionmentioning
confidence: 99%
“…The acquired skill level should be re-established after a period of non-use in which the recall of the skill was not required (Kluge & Frank, 2014). Refresher interventions can be implemented, for instance, as a practical rehearsal (Bjork & Bjork, 2006), in the form of tests (Roediger & Karpicke, 2006), or as a theoretical rehearsal (Cooper, Tindall-Ford, Chandler, & Sweller, 2001).…”
Section: Refresher Interventions and Skill Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy leads to superior memories in contrast to typical study practice (passive re-reading) approaches (Karpicke and Roediger, 2008; Roediger and Butler, 2011). On a side note it should be mentioned that studies using complex and dynamic learning material for controlling complex technical systems could, however, not observe the superiority of the testing- effect compared to additional practice (Kluge and Frank, 2014). Smith and colleagues reported that retrieval practice lead to superior memory performance.…”
mentioning
confidence: 99%